50 Years of the Clean Water Act: Can We Sustain Its Success? - Yoder, Chris (Maine Policy Review, 2023)
The effectiveness of the Clean Water Act in mandating the abatement of gross pollution by setting technology standards for categories of municipal and industrial point sources is well documented. Still, the CWA has not been modernized to update water quality standards, it has not readily employed the latest science, and the benefits have not been documented nearly well enough. Increasingly insidious attempts to undermine its continued effectiveness have arisen over the past 10–15 years mostly at the state level.